Effectiveness Test Digital Assessment based Moodle as a Digital Assessment Instrument for Measuring Science Literacy Skills for Junior High School Students - Permatasari, Annisaa Dwi Ayu; Handayani, Rif'ati Dina; Siswati, Bea Hana; Bachtiar, Ahmad Adam (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Objective: This study aims to test the effectiveness of Moodle-based Digital Assessment as an assessment instrument to measure scientific literacy possessed by junior high school students in Jember and Probolinggo, Indonesia especially on environmental pollution. Method: This type of research is development research with a 4D model that Defined, Designed, Developed, and Disseminated. The data analysis technique used descriptive analysis and calculation of scientific literacy. Result: For the results small-scale trial, most students were in the high category. The results of the large-scale test for junior high school in Jember, Indonesia show most students in the medium category. The results of the large-scale test for junior high school in Probolinggo, Indonesia show most students in the high category. The results of this study prove Digital Assessment developed is very effective for measuring the scientific literacy of junior high school students, especially regarding environmental pollution. Novelty: Researchers have never previously conducted research that developed a Moodle-based Digital Assessment to measure the scientific literacy skills of junior high school students.